The New Approach to The Source of Kalām Atomism - Cağfer Karadaş (ULUM, 2018)
‘Kalām atomism’ is one of the central subjects in the Mutakallimūn’s doctrine of universe. The origin of this subject still remains to be explored. Moses b. Maymonides claims that kalām atomism was affected by Greek atomism. This claim also has been taken into account by various orientalists. In the XIX. Century, Schmölders and Mabilleu claimed that Kalām atomism was effected by Indian atomism. Shlomo Pines in his Beitrage zur Islamischen Atomenlehrehas acknowledged a resemblance between the certain aspects of Greek and Kalām atomism. Pines thought that the difference between Greek atomism and Kalâm atomism were too great and therefore believed that the search for a source of Kalām atomism was inconclusive. Pines established some congruities between the doctrines of and Kalām atomism. According to Alnoor Dhanani in The Physical Theory of Kalām(Brill 1994)Pines failed to find possible routes transmission from the former of the latter. Before Pines (ten years ago), Şemseddin (Günaltay), in his article called “Mütekellimûn ve Atom Nazariyesi” (Daru’l-Funun İlahiyat Fakültesi Mecmuası, 1925) acknowledged congruities between the doctrines of Indian atomism and Kalām atomism. This article claims that Kalām atomism was put forward by mutekellimûnin and the influence of Greek and Indian atomism on Kalām atomism was indirect. Therefore Kalām atomism can be treated as an original theory.